Dark days in Salem : the witchcraft trials - Kent, Deborah (Movements and moments that changed America., 2021)
Describes the history of the Salem witch trials in 1692, discussing the history that led to the hysteria, information about the village and its people, and how the tragic events finally ended. Includes photographs and a timeline.